2007
DOI: 10.1007/bf03165785
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical analysis of L. tredecimguttatus venom collected by electrical stimulation

Abstract: The L. tredecimguttatus venom was collected by electrical stimulation and systematically analyzed. Gel electrophoresis and RP-HPLC showed that the venom consisted primarily of proteins with molecular weights above 10 kDa, most of which were high-molecular-mass acidic proteins, with fewer proteins and peptides below 10 kDa. The most abundant proteins in the venom were concentrated at around 100 kDa, which included latrotoxins- the principal toxic components of the venom. Injection of the venom in mice and cockr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…The protein content of the egg extract reached 34.22%, which was, however, lower than that (55.16%) of the venom secreted by the spider’s venomous glands [6], suggesting that the egg extract contains more non-proteinous components than the venom. Gel electrophoresis and mass spectrometric analyses showed that the eggs, like the venom [6], are composed mainly of large proteins and the content of low-molecular-mass proteins or peptides is relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein content of the egg extract reached 34.22%, which was, however, lower than that (55.16%) of the venom secreted by the spider’s venomous glands [6], suggesting that the egg extract contains more non-proteinous components than the venom. Gel electrophoresis and mass spectrometric analyses showed that the eggs, like the venom [6], are composed mainly of large proteins and the content of low-molecular-mass proteins or peptides is relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…The venom secreted by its venomous glands is a mixture of biologically active components which have diverse actions on prey as well as human victims. Many studies including our previous work analyzed the venom secreted by its venomous glands and described the biological properties and structures of some venomous proteins in the venom [26]. Interestingly, black widow spider, different from other poisonous animals, has toxic components not only in the venomous glands, but also in other parts of the body (such as legs and abdomen) and its eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Venom was collected using electrostimulation with 7V of AC current, similar to previous studies [21][22][23][24]. Anesthetized individuals were placed on clamped forceps attached to an electrode.…”
Section: Venom Collectionmentioning
confidence: 99%
“…L. tredecimguttatus spiders are highly poisonous and usually cause adverse reactions even lethal effects on humans and animals by envenomation [4], so ordinary people are afraid of the spiders while toxinologists are interested in them because all kinds of toxic components contained in poisonous spiders constitute a library of natural bioactive substances to discover and screen for pharmacological tool reagents, drug leads and insecticides [5,6,7]. As one of the most toxic spider species, the black widow spider differs from snake, scorpion and some other venomous spider species in that it has toxic components not only in its venomous glands [8,9,10,11] but also throughout its body, even in its newborn spiderlings and eggs [12,13,14]. Our research group has been using chromatography, proteomics, patch clamp and other related techniques to comprehensively analyze spider egg toxicity.…”
Section: Introductionmentioning
confidence: 99%